Gender and the environmental concerns of young farmers: Do young women farmers make a difference on family farms? - İlkay Unay-Gailhard; Štefan Bojnec (Journal of Rural Studies, 2021)
Although the visibility of women farmers in agriculture is increasing, we have little knowledge about the impact this will have on the environmental management of family farms. Numerous studies have documented that young women farmers show high concern for environmentally friendly farming practices relative to young male farmers. However, family farms are still a prominent business form globally, and it is still unclear whether or not we can expect young women farmers in different employment statuses (manager, or full-time farm worker and spouse) and work schedules (full- or part-time) to show any differences in the adoption of environmental practices compared to young male farmers. This study investigates the question of how increasing the visibility of women on family farms, and young women's sensitivity to environmental concerns relative to male's, plays out in the dynamic of adopting Agri-Environment-Climate Measures (AECMs). Our results confirm gender differences in AECM adoption behavior when we investigate the employment statuses of young women farmers; however, for part-time family farms, gender differences in the adoption behavior disappears, while they emerge for environmental subsidies received. We argue that gender aspects of the adoption behavior of AECMs contain several overlapping issues, particularly gender differences in the spouse's involvement in farm work.
Keywords: 330; young farmers; young women farm managers; agri-environment-climate measures (AECMs); family farms; part-time farms